PENINGKATAN MOTIVASI BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF NHT MAHASISWA PENDIDIKAN MATEMATIKA - Sumargiyani Sumargiyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
This research aims to improve learning motivation in Advance Calculus study by using the Number Head Together learning model Mathematics Education FKIP University of Ahmad Dahlan (UAD) year 2017/2018. This research is a classroom  action research. Subjects in this research is the B class of Mathematic Education  FKIP UAD 2017/2018 year 2017/2018 who take Advance Calculus course. Meanwhile, the object of the research is the application of  NHT learning model in Advanced Calculus courses in Mathematics Education  Study Program FKIP UAD year  2017/2018. The research was carried out as much as 2. Data collected by observation and questionnaire. The data used is quantitative descriptive analysis. The results shows that the NHT learning model can increase student’s learning motivation in duplicate integrals. This can be seen from the percentage of learning motivation in cycle I  by 64% (good) and cycle II 80% (very good). Keywords: motivation of learning, NHT, Advance Calculus